2018
DOI: 10.1016/j.energy.2018.08.206
|View full text |Cite
|
Sign up to set email alerts
|

The status of 4th generation district heating: Research and results

Abstract: Highlights:  Provides a review of 4 th Generation District Heating (4GDH) in scientific papers  Shows how 4GDH is an important integrated part of future sustainable energy systems  Quantifies costs and benefits of 4GDH in a future sustainable energy system  Shows how benefits exceed costs by a safe margin  Shows the significant benefits of systems integration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
158
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 463 publications
(192 citation statements)
references
References 72 publications
0
158
0
6
Order By: Relevance
“…Taking the interest of low temperature district heating investments into account, it is noted that, in Denmark, the 4DH research centre was active between 2012 and 2018 with contributions from several Danish and international universities, together with many Danish district heating and companies. Researchers within this centre have written a 4GDH definition paper ( [17]) and a 4GDH status paper ( [16]). Many papers have also been published in scientific journals from the annual international 4DH conferences since 2015 ( [15]).…”
Section: Denmarkmentioning
confidence: 99%
“…Taking the interest of low temperature district heating investments into account, it is noted that, in Denmark, the 4DH research centre was active between 2012 and 2018 with contributions from several Danish and international universities, together with many Danish district heating and companies. Researchers within this centre have written a 4GDH definition paper ( [17]) and a 4GDH status paper ( [16]). Many papers have also been published in scientific journals from the annual international 4DH conferences since 2015 ( [15]).…”
Section: Denmarkmentioning
confidence: 99%
“…The 4GDH concept has addressed this question [3,8]. The technical solution is to lower distribution temperatures with forward/return temperatures reduced to around 55/40 • C. Lower distribution temperatures allows access to larger amounts of waste heat from industries, increases the efficiencies of renewable heat sources, and increases the coefficient of performance (COP) of large-scale heat pumps when converting renewable-based electricity to heat [9,40,41]. The third element makes it possible for the district heating sector to balance the fluctuations from wind and solar electricity generation and provide access to large-scale heat storage units [42,43].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Facing this technological change in electricity production, district heating grids are risking being left as uncompetitive stranded assets. However, research addressing this issue has identified large potentials for district heating systems in a renewable energy system, the so-called fourth generation district heating (4GDH) system [8][9][10]. The strategic role of district heating in this vision-from which it may derive its future economic value-implies, among others, the ability to convert excess electricity from fluctuating renewables to heat at high efficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides work looking into providing flexibility for renewable electricity integration within the power sector, work on a cross-sectoral integration including all sectors and/or energy carriers has been published [2]. Hence, tools and approaches integrating different energy systems are needed [3]. For providing flexibility to the power system, energy storage systems are crucial.…”
Section: Introductionmentioning
confidence: 99%